Think again : why good leaders make bad decisions and how to keep it from happening to you - Finkelstein, Sydney; Whitehead, Jo.; Campbell, Andrew, 1950 August 3- (Boston, Mass. : Harvard Business Press, 2008)
Packed with compelling stories from various industries and disciplines, 'Think Again' offers illuminating insights on the potential flaws in how we all make decisions.
In the eye of the storm -- Pattern recognition -- Emotional tagging -- One plan at a time -- Misleading experiences -- Misleading prejudgments -- Inappropriate self-interest -- Inappropriate attachments -- Reducing risks with safeguards -- Selecting safeguards -- Leaders make good decisions.
Includes bibliographical references (pages [219]-230) and index.
Description based on print version record.
Keywords: Decision making; Leadership; Prise de décision -- Guides, manuels, etc; Prise de décision -- Cas, Études de; Leadership -- Guides, manuels, etc; Leadership -- Cas, Études de; Decision making; Leadership; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books